SAT0269 Survival of The Second TNF Inhibitor in Patients with Poly-JIA. (15th July 2016) - Bzarova, T.; Alexeeva, E.; Valieva, S.; Denisova, R.; Isayeva, K.; Sleptsova, T.; Chistyakova, E.; Chomahidze, A.; Lomakina, O.; Soloshenko, M.; Fetisova, A.; Kashchenko, E.
Abstract : Background: TNFα is one of the most important cytokine in the pathogeneses of poly-JIA. There are several TNF inhibitors for the treatment poly-JIA. Switching TNF-blockers is often strategy in the treatment of poly-JIA. Methods: An open observational study in patients with poly-JIA taking the second TNFinhibitor. A total of 119 patients (46 boys and 73 girls) were included in this study. The mean age was 11 (7;14), disease duration was 5 (3;8) years. By the switching time 54/119 had active polyarthritis, 58/119 – olygoarthritis, 7/119 – active uveitis without arthritis. Infliximab was the first TNF inhibitor in 105/119, adalimumab – in 3/119, etanercept – 11/119. 81/119 were switched to adalimumab, 38/119 – to etanercept. Analysis of survival the second TNF blocker treatment was performed in all patients by Kaplan–Meier curve. Results: The causes for cancellation of the first and second TNF blockers were second inefficacy (3, 7% and 8%), adverse events (5, 6% and 2, 5%) and administration causes (7% and 8%). Infliximab was cancelled because of primary inefficacy (7/105, 6.7%), second inefficacy (57/105, 54.3%), adverse events (12/105, 11.4%), relapse of uveitis (7/105, 6.7%), disease remission (19/105, 18.1%), administration causes (3/105, 2.8%). Etanercept was discontinued because of primary inefficacy (1/11, 9%), second inefficacy (2/11, 18%), adverse events (2/11, 18%), relapse of uveitis (6/11, 55%). Adalimumab was cancelled because of primary inefficacy (1/3), adverse events (1/3), administration causes (1/3). The second TNF inhibitor treatment survival in patients with the primary inefficacy of the first TNF inhibitor at 1, 2 year was 73%, at 1, 8 year was 73%, at 2, 4 year was 53%. The second TNF inhibitor treatment survival in patients with the second inefficacy of the first TNF inhibitor at 1, 2 year was 82%, at 1, 8 year was 82%, at 2, 4 year was 69%. The second TNF inhibitor treatment survival in patients with the remission of the first TNF inhibitor and relapse of disease at 1, 2 year was 82%, at 1, 8 year was 82%, at 2, 4 year was 72%. The number of AE was 32.2 and 24.5 per 100 p.y. on the 1st and 2nd TNF blocker treatment, accordingly (p<0, 0001). Conclusions: The highest percent of survival of the second TNF inhibitor treatment was registered in patients with poly-JIA whom the first TNF inhibitor was cancelled because of disease remission and the lowest percent – in patients with poly-JIA whom the first TNF inhibitor was cancelled because of the primary inefficacy of the first TNF inhibitor. Disclosure of Interest: T. Bzarova Grant/research support from: Pfizer, E. Alexeeva Grant/research support from: Roche, Novartis, UCB, S. Valieva Grant/research support from: Roche, R. Denisova Grant/research support from: Roche, Novartis, UCB, K. Isayeva Grant/research support from: Roche, Novartis, T. Sleptsova Grant/research support from: Novartis, UCB, E. Chistyakova: None declared, A. Chomahidze: None declared, O. Lomakina: None declared, M. Soloshenko: None declared, A. Fetisova: None declared, E. Kashchenko: None declared